Morphodynamics of a gravel beach protected by a detached low-crested breakwater. The case of Levanto (eastern Ligurian Sea, Italy) - Schiaffino, Chiara F.; Dessy, Claudia; Corradi, Nicola; Fierro, Giuliano; Ferrari, Nicola (Italian journal of engineering geology and environment, 2015)
During the last decades many researches were carried out to highlight interactions between detached low-crested breakwaters and beach morphodynamics. However, up to now, the infl uence of grain size on beach morphodynamic response to a breakwater has been scantily considered. This study focused on Levanto gravel beach, partially protected by a low-crested breakwater: the beach was observed through a video monitoring system, with the aim of underlining its morphological variations in connection to wave characteristics. According to collected Run up values, Levanto breakwater effectively protects the beach during mild wave perturbations (Hs < 0.5). As to the beach’s morphological response to the barrier, according to AHRENS & COX (1990) and POPE & DEAN (1986) formulae, a periodic tombolo or a permanent salient should form. Conversely, obtained results highlighted the formation of a periodic salient whose evolutionary phases were strictly dependent on wave height.